The Analysis of Workload and Safety Communication Against Burnout Syndrome in Inpatient Nurses - Yulia Purnawati1 , Tri Martiana2 , Rachmat Hargono3 , Firman Suryadi Rahman4 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction: Burnout is a psychological problem that attacks nurses and is one of the risks causes nurses to do unsafe actions. Nurses suffering from burnout and have a less safe environment will implement inefficient care systems. Generally, high workload is directly proportional to the incident of burnout. This research study aimed to find the effect of workload and safety communication on the level of burnout in inpatient nurse services. Method: This research was a cross-sectional study implemented at Rumah Sakit Umum Haji and Rumah sakit Islam Jemursari Surabaya, Indonesia. This implementation of research study was started in April to June 2019. The samples were collected using two populations of sampling method and got 138 nurses as samples. To analyze the effect of workload and safety communication on burnout syndrome, the researcher used multinomial logistics. Results: The results of Multinomial logistic test showed that workload affected the incidence of burnout with a value of p = 0.037 and safety communication did not affect the incidence of burnout syndrome with a value of p = 0.274. Conclusion: Workload affected the burnout syndrome incidence, while safety communication had no notable effect on burnout syndrome. The researcher suggests the hospitals to provide mental and physical health services, as well as stress coping training for nurses.